Fixed heigth S-band radar observations of the stratosphere - Ierkic, H.M. (1990)
It is now known that turbulence and mixing in the lower stratosphere occurs in intermittent layers of thickness between about 30 and 300 meters. Layered structures also exist in the ocean (Woods, 1969) and in the atmospheres of the other planets (Gierasch and Conrath, 1987). It appears that dissipative processes in stratified geophysical fluids frequently take place in thin layers. It is therefore of great importance to observe and document the nature of these dynamical regions. The Arecibo facility is uniquely capable of performing these high resolution measurements. The S-band radar system has been configured for high resolution studies of the lower stratosphere, and data have been collected and analyzed, demonstrating its potential and capabilities. Previous e:ffort was directed to a description of a wide region of the atmosphere, with only brief attention dedicated to continuous observations of a particular height. We propose a new series of observations focusing on the time evolution of waves and turbulence at a fixed altitude. The mode of operation that best meets this objective is "Fixed mode pointing," as described by lerkic et al. (1990) (attached as an Appendix), and no new techniques need to be developed.